Comportamento geográfico do voto : a identificação partidária em Portugal e no Brasil - Augusto, Daniel Cirilo (2017)
This research aims to analyze personal and political party identification in the vote decision of Portuguese and Brazilian voters. We tried to identify the importance of the political parties for the decision of the vote. The different scales of electoral lawsuits are used here to ascertain the different personal and partisan identification levels in the electorate. Methodologically, this work was developed through three axes: readings for the theoretical reference construction, interviews with Brazilian politicians and application of questionnaires to Portuguese and Brazilian voters. The following samples were selected: Braga, Évora and Lisboa (Portugal) and Curitiba, Laranjeiras do Sul and Maringá (Brazil). The research was conducted to understand the geographical behavior of the vote, through linkages (similarities and differences) between the Portuguese and Brazilian reality. The results presented reveal the decision of the vote based mainly on personal identification, with the exception of Portugal in national level elections, which obtained a considerable part of the voters to vote through party identification. In addition, it was concluded that the vote is hybrid, especially among the Brazilian electorate. The changes that occurred between the decision of the Brazilian voter's vote, allows us to identify that this voter has a character of change in his electoral decisions, making him sensitive to changes in the territorial context. Therefore, it is considered that the intrinsic elements of the territory (such as the electoral system, political parties, media, neighborhood effect, etc.), contribute to the partisan political environment formation, affecting the geographical behavior of vote.